Malignant melanoma.Review of 7 years (1998-2004) at Hospital Central of Funchal - Alves, Rubina (2007)
The authors reviewed all cases of melanoma diagnosed in the Hospital Central of Funchal, from January 1998 through December 2004. Fifty-one patients were studied, with ages ranging from 20 to 85 years. Sixty-five per cent were female. The most common anatom ical location in females was the lower limbs (45%) and in males the trunk (44%). At the time of diagnosis the majority of tumours were in stages I and II (57%). All patients were submitted to conventional surgery. Eighteen patients (35%) developed metastatic disease and 21 patients (41%) died (18 of whom from direct causes).